Answer:
we have added 9/4 to both sides of the equation.
Explanation:
The given equation is :
![x^2+3x=6](https://img.qammunity.org/2021/formulas/mathematics/high-school/vjcxodkx9vfk2z1s9cfrx3whyhjzwnwye6.png)
Here, a = 1, b = 3 and c = 6
We should add (b/2)^2 to the both sides of the equation.
(b/2)^2 = (3/2)^2 = (9/4)
![x^2+3x+(9)/(4)=6+(9)/(4)\\\\(x+(3)/(2))^2=(33)/(4)\\\\x+(3)/(2)=\pm (√(33))/(2)\\\\x= +(√(33))/(2)-(3)/(2), -(√(33))/(2)-(3)/(2)\\\\=1.37,-4.37](https://img.qammunity.org/2021/formulas/mathematics/high-school/458kl0d90lce4f8z9w1jvrbsxy4a5zgqtm.png)
Hence, we have added 9/4 to both sides of the equation.